2017
DOI: 10.1016/j.molmet.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal GLP1R activation limits adult adiposity by durably altering hypothalamic architecture

Abstract: ObjectiveAdult obesity risk is influenced by alterations to fetal and neonatal environments. Modifying neonatal gut or neurohormone signaling pathways can have negative metabolic consequences in adulthood. Here we characterize the effect of neonatal activation of glucagon like peptide-1 (GLP-1) receptor (GLP1R) signaling on adult adiposity and metabolism.MethodsWild type C57BL/6 mice were injected with 1 nmol/kg Exendin-4 (Ex-4), a GLP1R agonist, for 6 consecutive days after birth. Growth, body composition, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 65 publications
(91 reference statements)
1
10
0
Order By: Relevance
“…Neonatal exendin-4 protected against juvenile and adult rat myocardial ischaemic injury and preconditioned mitochondria ( Brown et al , 2010 ). Its administration in neonatal wild-type C57BL/6 mice prevented increased adult body weight and fat mass, and increased energy levels via GLP1R activation ( Rozo et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal exendin-4 protected against juvenile and adult rat myocardial ischaemic injury and preconditioned mitochondria ( Brown et al , 2010 ). Its administration in neonatal wild-type C57BL/6 mice prevented increased adult body weight and fat mass, and increased energy levels via GLP1R activation ( Rozo et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present findings provide evidence that chronic Ex4 treatment, in the presence or absence of OEA, incites an elevation in energy expenditure in the setting of obesity. Previous studies have suggested such an effect of chronic GLP-1R activation to elevate energy expenditure in rodents (32,48,62) and humans (3); however, in those studies, energy expenditure was only assessed toward the end of GLP-1RA treatment. To our knowledge, our studies are the first to measure these energy balance components continuously throughout the duration of treatment with OEA, Ex4, or the Ex4ϩOEA combination.…”
Section: R603mentioning
confidence: 99%
“…The incretin hormone glucagon-like peptide 1 (GLP1) is secreted postprandially by intestinal enteroendocrine cells to promote satiety and glucose-induced insulin release 46 . The administration of the GLP1-R agonist exendin-4 during the first week of postnatal life decreases the density of NPY fibers innervating the PVH and has a protective effect against both age-related and diet-induced obesity 47 . Moreover, genetic deletion of Glp1r in Sim1 neurons of the PVH reduces AgRP/NPY projections, while it increases POMC projections to the PVH 47 .…”
Section: Glp1mentioning
confidence: 99%